Ecobiology of Danaus chrysippus (Linnaeus, 1758) (Lepidoptera: Nymphalidae, Danainae) throughout the autumn – early winter breeding period on Rodos Island, Greece - Galanos, Christos (ENTOMOLOGIA HELLENICA, 2022)
The present study is focused on the biology and ecology of Danaus chrysippus on Rodos Island, Greece, contributing on the knowledge of its life cycle in nature throughout the autumn – early winter breeding period, which is described and illustrated here for the first time for the country. Distribution range, habitat requirements and larval hostplant preferences, which are closely related with specific microclimatic conditions and the availability of milkweed resources in the region, are discussed.